1994
DOI: 10.1055/s-0038-1648843
|View full text |Cite
|
Sign up to set email alerts
|

Activation of Blood Coagulation after Abrupt or Stepwise Withdrawal of Oral Anticoagulants - A Prospective Study

Abstract: SummaryThe occurrence of a “rebound hypercoagulable state” in patients after discontinuation of oral anticoagulants is still a matter of debate and no definite recommendation can be made on the best procedure for anticoagulant withdrawal. The present study investigated the changes in the levels of markers of activated blood coagulation in 32 patients (pts) in whom warfarin treatment (for venous thromboembolic disease) was randomly withdrawn abruptly (n = 17, group A) or gradually (n = 15, group B: ⅔ of initial… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
72
0

Year Published

2000
2000
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 102 publications
(75 citation statements)
references
References 21 publications
(10 reference statements)
3
72
0
Order By: Relevance
“…For example, it is known that the onset of cardiovascular events or cerebral infarction increases approximately three times by stopping antiplatelet therapy (27,28), and the development of serious thromboembolism following the discontinuation of anticoagulant therapy has been reported in several conditions (29)(30)(31). A recent report showed that significant risk factors for delayed bleeding include a reduced platelet count, extended prothrombin time, large extent of resection and positive/indeterminate lateral margin (32).…”
Section: Discussionmentioning
confidence: 99%
“…For example, it is known that the onset of cardiovascular events or cerebral infarction increases approximately three times by stopping antiplatelet therapy (27,28), and the development of serious thromboembolism following the discontinuation of anticoagulant therapy has been reported in several conditions (29)(30)(31). A recent report showed that significant risk factors for delayed bleeding include a reduced platelet count, extended prothrombin time, large extent of resection and positive/indeterminate lateral margin (32).…”
Section: Discussionmentioning
confidence: 99%
“…143 Five small controlled trials (total n 5 217) have addressed this issue. [144][145][146][147] The primary outcomes of four of the studies were laboratory results suggestive of a hypercoaguable state 144,145,147,148 and produced inconsistent results. Elevations tended to persist for 8 to 9 weeks, regardless of discontinuation strategy, suggesting an unmasked prothrombotic state in the absence of anticoagulant protection rather than a rebound phenomenon associated with abrupt discontinuation.…”
Section: Vka-discontinuation Of Therapymentioning
confidence: 99%
“…[144][145][146][147][148] The only major hemorrhage occurred in the gradual withdrawal group. Gradual discontinuation of VKA is likely to be more confusing and inconvenient for the patient.…”
Section: Vka-discontinuation Of Therapymentioning
confidence: 99%
See 1 more Smart Citation
“…There is longstanding controversy over the phenomenon of rebound hypercoagulability after the cessation of anticoagulation. 1 Although some studies do seem to confirm that there is activation of the coagulation system shortly after interruption of therapy, [2][3][4] it is unclear if this phenomenon is clinically meaningful, or how important it would be in the context of a brief periprocedural interruption. For example, a meta-analysis of studies of patients with venous thromboembolism (VTE) found that there is a transient increase of 2% in the rate of recurrent VTE during the 2 months after cessation of anticoagulant therapy.…”
Section: The Problem: How To Treat Patients During Interruptions Of Amentioning
confidence: 99%